Otorhinolaryngological manifestations in Traumatic brain injury in a tertiary care center of western Nepal - Rai, Shiwani; Yogi, Nikunja; Karmacharya, Balgopal; Maharjan, Manita; Koirala, Krishna (Journal of Brain and Spine Foundation Nepal, 2021)
Introduction: Otorhinolaryngological injuries in head injury are something which are very common but yet are overlooked, missed and at times forgotten. In this study, we tried to see the epidemiological characteristics, clinical presentations and management of these associated injuries in cases of head injuries in a tertiary care center in western Nepal. Methods: An analytical study was done in all cases of head injury admitted to neurosurgical ward and ICU in between January 2019 to December 2019. Various clinical and epidemiological details were collected from the patient’s records obtained from Medical Records Department and charted in a preformed performa. All the continuous data were presented in terms of mean and standard deviation and categorical data in terms of percentage. Statistical analysis was done using SPSS 22.0 software. Results: Soft Tissue lacerations were the commonest findings in all head injuries; nose and face lacerations (29.5%), ear lacerations (23.5%) followed by facial bone fractures (19.2%). There were 41(52.6%) cases with mild head injury, 23 (29.5%) cases with moderate head Injury and 17 (17.9%) cases with severe head injury in patients those had associated ENT findings. There was no any statistically significant difference in outcome or hospital stay in between the head injuries with and without ENT manifestations (p=0.187) and (p=0.219) respectively. Conclusion: Skull base tumors are treated based on findings of diagnostic nasal endoscopy and imaging results. CT scans and MRIs are becoming more significant in the diagnosis of diseases. Endoscopic techniques to the skull base were beneficial in treating the malignancy. Chemotherapy can be used as a gold standard first-line treatment with radiation and surgery for significant types of head and neck tumors. immunotherapy-like checkpoint inhibitors targeting PD1 are the second-line treatments of advanced HNSCC. Prospective research and trials will be required in the future.